KATA SERAPAN BAHASA INGGRIS DALAM BAHASA INDONESIA : KAJIAN MORFOLOGI DAN SEMANTIK - , DIAN NOVIANI SYAFAR, Dr.F.X Nadar, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is entitled English Loanwords in Bahasa Indonesia : Morphological and Semantic Analysis which analyzing English loanwords in Bahasa Indonesia based on morphological and semantic analysis. The data are some terrms used especially in economical, political and cultural fields found in newspaper. The theory of borrowing which consists of morphological and semantic analysis is applied in this research. Haugenâs theory (1972) about the process of borrowing that can be classified into importation and substitution process become the main reference. This research is aimed at classifying the types and forms of English loanwords, describing the semantic changes and identifying the reasons of using loanwords in Bahasa Indonesia. There are some conclusion can be stated after analyzing the data